IMPLEMENTATION OF THE STORYTELLING METHOD USING THE BIG BOOK AS AN ATTEMPT TO INCREASE KINDERGARTEN TEACHERS’ STORYTELLING SKILLS AT BUKIT RAYA PEKANBARU - Rospanizar Rospanizar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper is based on the Kindergarten teachers’ skill lack of storytelling at Bukit Raya Pekanbaru. It can be seen from the initial survey that the researchers conducted indicate that most of the teachers are evidently not skilled at storytelling yet properly. Of the 18 teachers who test their storytelling skills, only 53.3% were skilled at storytelling well. Conversely, 46.7% are not skilled at storytelling yet properly. The purpose of this paper is to find out the increase in teachers’ storytelling skills after applying the storytelling method using the big book, which was conducted at a kindergarten in Bukit Raya Pekanbaru. The type of research uses School Action Research. Based on the results of the data presentation and discussion, it can be concluded that the implementation of the storytelling method using the big book can improve kindergarten teachers’ storytelling skills in Bukit Raya Pekanbaru. It is indicated from the research findings that in the pre-cycle the average score of teachers’ storytelling skills was only 53.3%. After applying the storytelling method in cycle I, teachers’ storytelling skills increased to 73.3%. After conducting reflection and improvement in cycle II, the average score increased to 88.9%. Thus, the hypothesis in the research was accepted, which indicates that "there is an increase in Kindergarten teachers’ storytelling skills through the storytelling method using big books in Bukit Raya Pekanbaru".